Urban morphology and identity: The dock spaces of Melaka on the maritime silk road - Zhihui, Mo (The Journal of City: Branding and Authenticity, 2024)
Background: This research investigates the intricate relationship between historical docks and the urban development of Melaka, a significant maritime entrepot along the Maritime Silk Road. Focusing on the physical connections and urban morphological performance, this study explores how these docks have influenced the urban morphology and architectural typology of Melaka from its earliest settlement to the present. Method: Utilizing a multidisciplinary approach that combines urban planning, architectural analysis, historical research, and extensive fieldwork, this research identifies key dock spaces along the Melaka River and examines their connections to the city's inland areas. Through historical mapping and analysis of lost docks and market spaces, as well as religious buildings, the study reveals the complex interactions between these maritime infrastructures and urban development. Result: The findings highlight numerous challenges in preserving these historical nodes, including issues related to modern urban integration and conservation. Conclusion: The research concludes with recommendations for the conservation and management of these historical sites, emphasizing their importance in preserving Melaka’s historic urban landscape. By safeguarding these cultural heritage nodes, Melaka can maintain its urban identity and continue to honor its rich maritime history. Novelty/Originality of this study: The development of a comprehensive and adaptive maritime heritage integration model in modern urban planning, which combines urban morphology, historical mapping, and socio-economic impact assessment, provides a multidimensional framework for urban planners to preserve and revitalize infrastructure nodes while accommodating contemporary urban development needs, thereby creating a balance between heritage preservation and urban progress.